Filtration of soot-in-oil aerosols: Why do field and laboratory experiments differ? - Bredin, Arne; O'Leary, Rebecca; Mullins, Benjamin (Pergamon, 2012)
This work has investigated the impact of different oil ageing mechanisms which typically occur in diesel vehicles (thermooxidative breakdown and particle contamination) on engine lubricant properties and their subsequent influence on the filtration of the combined or colloidal (i.e. solid and liquid particles) aerosol, using fibrous filters. Oil viscosity was found to increase with increasing soot contamination and decrease with thermooxidative breakdown of the oil. Filtration tests showed that the pressure drop across the filter correlated strongly with oil viscosity and increased linearly with increasing soot content in the oil. Concurrent to the laboratory work, a field test using 15 diesel vehicles was conducted. The vehicles were equipped with test filters identical to the laboratory test filters and were used for approximately 6 months without oil change. The filters were then analysed and it was found that the final pressure drop also increased linearly with the soot content in the filter. A comparative analysis showed a good agreement in pressure drop, filter saturation and filter efficiency between laboratory and field test filters, for similar soot contents. It was found that the use of artificial oil ageing, combined with a discontinuous filtration method developed previously allowed reproduction (in the laboratory) of the filtration processes which occur in vehicle closed crankcase ventilation (CCV) systems. This therefore allowed “realistic” CCV tests to be conducted in a laboratory. It is hoped that this work will, at least partially, bridge the gap between laboratory and field filtration studies, as well as improving the knowledge of “colloid” or “soot-in-oil” aerosol filtration, which to-date has received limited study.